The teaching-learning process of a student with autism: a case study in an inclusive school - SILVA, Charles Lima; FACIOLA, Rosana Assef; PEREIRA, Rosamaria Reo (Faculdade de Filosofia e Ciências, 2018)
The concern about inclusive education has grown simultaneously with the increased presence of students with disabilities in regular schools. Following an international trend, the Brazilian government legislated for inclusive education, assuring the right of enrolling students with disabilities in regular schools. Among the great number of students with disabilities present in classrooms there are the ones with autism. People with autism usually show problems in language acquisition, oral production and socialization. Therefore, this study aims to investigate how the teaching-learning process in English classes occurs to autistic students. Thus, it is intended to ascertain the role of the teacher to actualize the process of inclusion, the challenges that arise from it, and which strategies are used to help the students overcome their limitations. This is a qualitative, exploratory and descriptive research, in the form of a case study. The data was collected through a semi-structured interview with an English teacher and through unstructured observations. The data was analyzed qualitatively from the content analysis technique and the results are presented in four thematic axes. The results show that, although the English teacher does not have adequate training, she finds support with the student’s family and the specialists in inclusive education in the school. As for the strategies used, they seemed to be effective due to the student’s response and production. It is expected that the findings may contribute to the understanding of the issue addressed, and the strategies cited may help English teachers to improve their pedagogical practices.